Sono-Enzymatically Embedded Antibacterial Silver-Lignin Nanoparticles on Cork Filter Material for Water Disinfection - Bermeo, Lizeth (2022)
Fil: Fil: Bermeo, Lizeth. Unesco Chair on Sustainability. Universitat Politècnica de Catalunya. Escola Superior d'Enginyeries Industrial, Aeroespacial i Audiovisual de Terrassa (ESEIAAT); Spain.